Efektivitas Game “Siapakah Aku” pada Wordwall Guna Mengembangkan Pengetahuan Peserta Didik dalam Bidang Bahasa Indonesia - Rahma Novia Budiati; Noer Adhela Krisna Putri Achmad; Fernanda Maulana Kusuma Putri; Veronika Deta Junia Anjarwani; Nensy Megawati Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study analyzes the effectiveness of digital educational games, particularly the “Who Am I?” game on the Wordwall platform, in enhancing students’ knowledge of Indonesian language learning. The research is motivated by the need for junior high school teachers to design engaging learning methods that can foster enthusiasm among adolescents. Educational games are viewed as innovative media that present concepts in a simple yet enjoyable way, making lessons more interactive and accessible. Using a descriptive quantitative approach, the study involved 30 eighth-grade students at SMP Negeri 38 Surabaya. Data collection included pre-tests and post-tests to quantitatively measure learning outcomes, as well as questionnaires to capture student responses. Findings indicate a notable improvement in student achievement after the application of the “Who Am I?” game. The average pre-test score was 71.33, which rose to 91.00 on the post-test, showing an increase of 19.67 points. Results of a paired t-test confirmed that the difference was statistically significant, demonstrating that the improvement was due to the intervention. Additionally, questionnaire results showed that students felt more motivated, engaged, and able to understand the material more effectively through this game. Overall, the “Who Am I?” game on Wordwall proved to be an effective learning tool, and its use is recommended for teachers seeking to implement game-based strategies in classroom instruction.